Pengaruh Sarana Prasarana dan Motivasi Belajar terhadap Hasil Belajar Siswa Kelas XII Otomatisasi Tata Kelola Perkantoran di SMK Ketintang Surabaya - Ainun Nisa Dwi Cintya; Jaka Nugraha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this study, 1) to determine the effect of school facilities and infrastructure on student learning outcomes in class XII OTKP in SMK Ketintang Surabaya, 2) to determine the effect of learning motivation on student learning outcomes in class XII OTKP in SMK Ketintang Surabaya, 3) to determine the effect of infrastructure and learning motivation on student learning outcomes in class XII OTKP in SMK Ketintang Surabaya. This research uses quantitative research with descriptive methods. The population in this study amounted to 159 students of class XII OTKP at SMK Ketintang Surabaya. Based on data analysis techniques found there is a significant influence of infrastructure on learning outcomes. This can be seen from the results of the t test at X1 significant value of 0.017 <0.05 which means the hypothesis is accepted. The results of this study indicate that it has a significant effect on learning outcomes. This can be seen from the results of the T test at X2 significant value of 0.047 <0.05 so that the hypothesis is accepted. Thus the presence of learning motivation in a person is very much needed to improve student learning outcomes. There is an influence of infrastructure and learning motivation on the learning outcomes of class XII students majoring in OTKP at SMK Ketintang Surabaya, which is positive at 61.40%. While the remaining 38.6% is influenced by other variables not examined in this study.